Visualization Analysis of Research Hotspots of Breast Cancer Microenvironment Based on CiteSpace and VOSviewer - Fang, Yuhang; Xie, Yi; Yang, Shuhan; Liu, Suying; Fang, Liyuan; Wang, Yan; Wang, Runxi; Zhang, Ying (Zhongliu fangzhi yanjiu, 2024)
Objective To explore the status of knowledge graph-based research into breast cancer microenvironment and to predict future research hotspots. Methods The literature related to breast cancer microenvironment in recent 20 years was retrieved from CNKI and Web of Science Core Collection database and analyzed with CiteSpace and VOSviewer. Results A total of 825 Chinese articles and 16,221 English articles were retrieved. Visual analysis showed that research focus has gradually shifted from cellular research to molecular research and drug innovation. Cancer stem cells, PD-1, PD-L1, immune checkpoint inhibitors,and nanoparticles are the main subjects of interest in research on breast cancer microenvironment, and the United States has the largest number of studies on breast cancer microenvironment, followed by China and Italy. Conclusion Current research mainly focuses on tumor stemness, immunotherapy, and nanodelivery. Owing to deepening research in this field, the targeting of the breast cancer microenvironment f